Induction of Labour in Nulliparous Women Beyond Term in a Low-Risk Population - Pretscher, Jutta; Weiss, Christel; Dammer, Ulf; Stumpfe, Florian; Faschingbauer, Florian; Beckmann, Matthias; Kehl, Sven (Zeitschrift für Geburtshilfe und Neonatologie, 2019)
Purpose To evaluate the influence of gestational age on induction of labour in nulliparous women.
CRIS-Team WoS Importer:2019-03-15